A noble masquerade eaudiobook Hawthorne house series, book 1. - Hunter, Kristi Ann (Hawthorne House, 2015)
Sparkling Regency Romance from a Captivating New Voice Lady Miranda Hawthorne acts every inch the lady, but inside she longs to be bold and carefree. Entering her fourth Season and approaching spinsterhood in the eyes of society, she pours her innermost feelings out not in a diary but in letters to her brother's old school friend, a duke-with no intention of ever sending these private thoughts to a man she's heard stories about but never met. Meanwhile, she also finds herself intrigued by Marlow, her brother's new valet, and although she may wish to break free of the strictures that bind her, falling in love with a servant is more of a rebellion than she planned. When Marlow accidentally discovers and mails one of the letters to her unwitting confidant, Miranda is beyond mortified. And even more shocked when the duke returns her note with one of his own that initiates a courtship-by-mail. Insecurity about her lack of suitors shifts into confusion at her growing feelings for two men-one she's never met but whose words deeply resonate with her heart, and one she has come to depend on but whose behavior is more and more suspicious. When it becomes apparent state secrets are at risk and Marlow is right in the thick of the conflict, one thing is certain: Miranda's heart is far from all that's at risk for the Hawthornes and those they love.